Musculoskeletal Disorders and Ergonomic Factors among the Cabin Crews of the National Airline of Bangladesh - Sk Akhtar Ahmad; Taslima Akhtar; Mahmud Hossain Faruquee; Saika Nizam; Rabeya Yasmin; Sarmin Sultana; Israt Jahan; Ali Kamal Mostofa Rubel; AKM Masum Ul Alam (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Cabin crews on aircraft are at risk of developing musculoskeletal disorders as a result of their workload and the nature of their profession. This study is an attempt to identify work-related musculoskeletal disorders suffered by cabin crews and the associated ergonomic factors. Methods: This was a cross-sectional study conducted among the cabin crews. The cabin crews, regardless of gender, who had worked at least one year, were selected by simple random sampling. A total of 246 cabin crews were the respondents in this study. A Nordic Musculoskeletal Questionnaire was used to assess the respondents' MSDs. To determine the predictors of MSDs, a binary logistic regression analysis was performed. Results: Out of 246 cabin crew, 55.3% were males, and the mean age was 39.83±9.289 years. The mean flight duration was 85 hours, and the maximum flying hours was 123. Of the total participating crews, more than half (55.7%) suffered from musculoskeletal disorders (MSDs). The common sites of MSDs were the low back, shoulder, neck, and knee joints. Poor ergonomic factors such the increasing age and flight duration were also contributing factors to MSDs. Conclusion: The study revealed that over half of the cabin crew suffered from work-related musculoskeletal disorders. A number of ergonomic factors, including age and flight duration, were found to be associated with MSDs.